2015
DOI: 10.4236/abc.2015.54016
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical and Microbiological Analysis of Potable Water in Jericho and Molete Areas of Ibadan Metropolis

Abstract: This study was carried out to determine the quality of some water supplies in Jericho and Molete areas in Ibadan, Oyo State, Nigeria. A total of 6 water samples (Jericho and Molete) from well, borehole and public tap were randomly selected and analyzed in triplicate for some physico-chemical and microbial parameters. The pH ranged from 5.88 ± 0.01 to 6.88 ± 0.06 while total hardness ranged from 2.60 ± 0.04 ppm to 44.00 ± 1.20 ppm. The temperature ranged from 15.00˚C ± 0.07˚C to 18.00˚C ± 0.21˚C while conductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Hard water reduced mortality from heart diseases 12 thus apparently supporting the relatively lower contamination load of the downstream sample as oted with the BOD, COD and OD results of this study and the inference thereto. High DO as noted in the downstream sample suggested lower pollution status 10 hence better water quality. Nevertheless, organic matter contamination of the three-point samples of waterside River, Aba was suggested due to the relatively lower COD value observed in this study compared to that (30 mg/L O 2 ) for Sokoto River.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Hard water reduced mortality from heart diseases 12 thus apparently supporting the relatively lower contamination load of the downstream sample as oted with the BOD, COD and OD results of this study and the inference thereto. High DO as noted in the downstream sample suggested lower pollution status 10 hence better water quality. Nevertheless, organic matter contamination of the three-point samples of waterside River, Aba was suggested due to the relatively lower COD value observed in this study compared to that (30 mg/L O 2 ) for Sokoto River.…”
Section: Resultsmentioning
confidence: 80%
“…In particular, high DO as noted in the Downstream sample suggested lower pollution status. 9,10 Generally, BOD, the amount of dissolved oxygen required for the biochemical decomposition of organic compounds and the oxidation of inorganic materials, particularly for the Downstream sample was higher than the EPA standard and 2.13 mg/L O 2 for Sokoto River. 11 The higher (p<0.05) TH (mg/L CaCO 3 ) of the Downstream sample (20.04±0.01) compared to the Midstream (0.99±0.00) and Upstream (0.61±0.00) samples though lower (p<0.05) than that for the standard (500.00) indicated that the samples were not, though the Downstream sample is more likely to be, hard.…”
Section: Resultsmentioning
confidence: 86%
“…In rural locations where water sources are communally shared and exposed to several fecal-oral transmission channels in their local boundaries, bacterial contamination of drinking water is a primary cause of water-borne infections (Gwimbi et al, 2019). The contamination of the water can also be linked to the presence of pathogens such as fecal coliforms and Escherichia coli (Ladokun and Oni, 2015). They can therefore be viewed as a sign of fecal contamination and potentially declining water quality when found in drinking water.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial contamination of drinking water is a major contributor to water-borne diseases in rural areas where water sources are communally shared and exposed to multiple fecal-oral transmission pathways in their neighborhood boundaries (Gwimbi et al, 2019). The contamination of the water can also be traced to the presence of pathogens such as fecal coliforms and Escherichia coli (Ladokun and Oni, 2015). Their presence in drinking water can thus be seen as an indication of fecal pollution and possible deteriorating water quality.…”
Section: Introductionmentioning
confidence: 99%